De novo variation in EP300 gene cause Rubinstein-Taybi syndrome 2 in a Chinese family with severe early-onset high myopia - Xiaoyu Huang; Xue Rui; Shuang Zhang; Xiaolong Qi; Weining Rong; Xunlun Sheng (BMC, 2023)
Abstract Background Rubinstein-Taybi syndrome (RSTS) is characterized by distinctive facial features, broad and often angulated thumbs and halluces, short stature, and moderate-to-severe intellectual disability, classified into two types RSTS1 (CREBBP-RSTS) and RSTS2 (EP300-RSTS). More often, the clinical features are inconclusive and the diagnosis of RSTS is established in a proband with identification of a heterozygous pathogenic variant in CREBBP or EP300 to confirm the diagnosis. Methods In this study, to describe an association between the clinical phenotype and the genotype of a RSTS2 patient who was initially diagnosed with severe early-onset high myopia (eoHM) from a healthy Chinese family, we tested the proband of this family by whole exome sequencing (WES) and further verified among other family members by Sanger sequencing. Real-time quantitative PCR was used to detect differences in the relative mRNA expression of candidate genes available in the proband and family members. Comprehensive ophthalmic tests as well as other systemic examinations were also performed on participants with various genotypes. Results Whole-exome sequencing revealed that the proband carried the heterozygous frameshift deletion variant c.3714_3715del (p.Leu1239Glyfs*3) in the EP300 gene, which was not carried by the normal parents and young sister as verified by Sanger sequencing, indicating that the variant was de novo. Real-time quantitative PCR showed that the mRNA expression of EP300 gene was lower in the proband than in other normal family members, indicating that such a variant caused an effect on gene function at the mRNA expression level. The variant was classified as pathogenic as assessed by the interpretation principles of HGMD sequence variants and ACMG guidelines. According to ACMG guidelines, the heterozygous frameshift deletion variant c.3714_3715del (p.Leu1239Glyfs*3) in the EP300 gene was more likely the pathogenic variant of this family with RSTS2. Conclusions Therefore, in this paper, we first report de novo heterozygous variation in EP300 causing eoHM-RSTS. Our study extends the genotypic spectrums for EP300-RSTS and better assists physicians in predicting, diagnosis, genetic counseling, eugenics guidance and gene therapy for EP300-RSTS.